Relativistic magnetron with microsecond pulse lengths; Soviet Technical Physics Letters; Vol. 4, № 7 - Didenko A. N.; Sulakshin A. S.; Svirko Yu. P.; Fomenko G. P.; Tsvetokov V. I.; Yushkov Y. G. Yuri Georgievich (1978, 1978)
В фонде НТБ ТПУ отсутствует